Efficacy and safety of levetiracetam for migraine prophylaxis in children: a systematic review and meta-analysis - Jing Peng; Linhui Liu; Qiaoling Li; Maochang Liu; Rong Zhou; Li Chen; Zhisheng Liu (Frontiers Media S.A., 2024)
BackgroundLevetiracetam (LEV), an antiepileptic drug, has been effective in adult migraine prevention but lacks extensive research in children. This study evaluates LEV's efficacy and safety for pediatric migraine prophylaxis.MethodsWe reviewed randomized controlled trials (RCTs) and non-RCTs in major databases through 8 January 2024, focusing on four efficacy endpoints and adverse drug reactions (ADRs). Data synthesis involved pooled relative risks or odds ratios for dichotomous outcomes and mean differences for continuous outcomes, using fixed- or random-effects models as appropriate.ResultsEight studies with 190 participants showed that after taking LEV, the mean headache frequency decreased 5.19 per month (MD: −5.19, 95% CI: −7.11 to −3.27, p < 0.00001) and improved headache-free rates to 28% (95% CI: 0.17-0.41). More than 83% experienced a >50% reduction in monthly headache frequency. The migraine disability score decreased by 33.51 points (MD: −33.51, 95% CI: −38.46 to −28.55, p < 0.00001). ADR incidence did not significantly differ between LEV and control groups (RR: 1.06, 95% CI: 0.39 to 2.85, p = 0.91), with an overall ADR rate of 18% (95% CI: 0.13-0.24). The most common ADR was irritability (12%), leading to treatment discontinuation in 13% of cases (95% CI: 0.05-0.30).ConclusionLEV has shown good efficacy in preventing pediatric migraines. However, its safety requires further confirmation through more extensive and well-designed RCTs.Systematic Review RegistrationIdentifier PROSPERO CRD42024497643.